Pendampingan Sosialisasi Dampak Negatif Gadget Pada Anak Sekolah Dasar Kelas V dan VI di SDN 2 Nambangrejo, Desa Nambangrejo Kecamatan Sukorejo Kabupaten Ponorogo - Nalailul Mukaromah; Khafidhoh Khafidhoh; Miftaku Ni'amah (Institut Agama Islam Sunan Giri Ponorogo, 2025)
The service that we carry out by assisting in the socialization of the negative impacts of Gadgets aims to prevent the negative impacts that arise due to excessive use of Gadgets and minimize their use on children in Dukuh Tengah, Nambangrejo Village, specifically the students at SDN 2 Nambangrejo. The method used is Asset Based Community Development (ABCD). The results achieved from this service are that children can reduce their activity of playing Gadgets, as can be seen from the children who prefer to play with their peers in their neighborhood and with the KPM team rather than playing Gadgets. There is a use of time after school, which can be seen from the children being more active in taking part in madin activities, reciting the Iqro' Koran, juz amma, al Qur'an, memorizing letters, practicing giving speeches in the mosque or prayer room in the neighborhood. The increase in children's interest in learning can be seen when they attend tutoring with the KPM team at night with focus, not using their smartphones to play games.